The Importance of the Noahic Covenant to Biblical Theology - Chalmers, Aaron (Tyndale bulletin, 2009)
This article seeks to draw attention to the importance of the Noahic covenant to biblical theology. This article suggests that rather than being of only marginal significance, the Noahic covenant is of decisive importance for understanding the broader metanarrative of Scripture. In particular, this covenant establishes the basis or foundation for the story (God’s commitment to creation, and in particular, the preservation of life on earth), establishes the parameters of the story (God’s activity reaches out to embrace not only humanity, but also the created animals and the earth), and provides an anticipation of the conclusion of the story of redemption (God’s judgement on sin, salvation of the righteous, and renewal of creation).